(untitled) (Journal of Material Science and Technology Research, 2022)
Abstract: Fe1-xMnxS thin films with concentration x=0.02, 0.04, 0.06, 0.08, 0.1 have been deposited on glass substrates by a simple Chemical Bath Deposition (CBD) method at 90 oC. The X-ray Diffraction analysis of deposited thin films revealed the growth of mono-phasic mackinawite (FeS) structure with crystallite size in the range from 4.06 to 5.95 nm as a function of manganese concentrations. The other structural parameters like stacking faults, dislocation density and lattice strain affirmed the improvement in crystal structure and phase stability in manganese doped FeS thin films. Scanning Electron Micrographs depicted the growth of nano-flakes and nano-flowers in case of pure FeS thin films while for manganese doped iron sulfide thin films, homogeneity of the deposited material was observed to improve with distinct boundaries of almost spherical nanostructures. The direct energy band gap of FeS mono-phasic thin films was observed to decrease from 2.23 to 1.89 eV as the concentration of manganese increases in host lattice. The prepared thin films with tunable optical properties would have potential applications in energy conversion and optoelectronic devices.